The adverse effects of policing on population health: A conceptual model. (July 2021) - Simckes, Maayan; Willits, Dale; McFarland, Michael; McFarland, Cheryl; Rowhani-Rahbar, Ali; Hajat, Anjum
Abstract: While negative encounters between police and the community are not a new trend, recent high profile deaths of unarmed people of color have gained widespread national attention and ignited new movements demanding reform, accountability, and progress. Increasingly over the past few decades, researchers have examined the most extreme cases of lethal use of force, describing the context of these violent encounters, situational and personal characteristics, and underlying risk factors. More recent research has aimed to define the broader and more nuanced adverse effects that policing can have on population health. We propose a holistic and multidisciplinary model for the relationship between policing and population health in the U.S. that incorporates contextual, situational, and individual-level factors while also recognizing the direct and vicarious mechanisms by which policing exposures can negatively affect population health. The model captures the short and long term health effects of policing and the cyclic nature by which those effects at the individual, community, and systemic levels can influence each other. We consider the unique qualities of different communities that may influence these pathways, the historical trends of the criminal justice and policing systems, and recommend applications of the model in policing agencies, medicine, and research. Highlights: Exposure to law enforcement comes in many forms, from arrest to social media. Adverse police encounters have direct and indirect effects on population health. Policing affects individuals, communities, and systems. Population health effects of policing can manifest in the short and long term. Research must account for societal, historical, agency, and contextual factors.